Ivan Fedorovich Leontiev – voivode and royal hunter at the court of Mikhail Romanov - Rabinovich, Yakov N. (Известия Саратовского университета. Новая серия. Серия: История. Международные отношения)
The article presents for the first time the biography of Ivan Fedorovich Leontiev, who was the father of one of the governors of Saratov. Brief information about his ancestors is provided. I. F. Leontiev began his service back in the Time of Troubles, as a representative of the Kashirsky “military city”, fought as part of the army of Prince M. V. Skopin-Shuisky. At the court of Tsar Mikhail Romanov, I. F. Leontiev served as a solicitor, a steward and a royal hunter. At the beginning of the Smolensk War, he was a voivode in Yelets. Special attention is paid to the last period of his life, when, as a royal hunter (1635–1647), he organized bear fights. A description of his land holdings is given, among which the village of Lukino, currently the famous Peredelkino.